Investigating the viability of lithium-ion battery - fuel cell hybrid systems - A case study for Greenland and Qatar - Witt, Hannes (UiT The Arctic University of Norway, 2020)
Renewable means of energy production have recently become cost competitive with fossil fuels. However, before they can be completely phased out, the issue of storing renewable energy must be addressed. Two energy storage technologies that have gotten a lot of attention over the past years are lithium ion batteries and hydrogen energy storage. Each of these technologies have their advantages, lithium ion batteries are generally cheaper than the fuel cells and electrolysers typically needed in hydrogen energy storage, while also having a greater roundtrip efficiency. Hydrogen storage containers for compressed hydrogen can, however, be manufactured such that the costs per kwh are below that of current lithium ion batteries. This makes hydrogen storage more attractive for long the long term, where greater energy capacity is needed, while lithium ion batteries become more attractive within a shorter time frame requiring less energy storage capacity and greater efficiency. A hybrid system relying on both hydrogen and lithium ion battery may thus be viable for situations in which both short- and long-term energy storage is required. The viability of such a hybrid system is investigated in this thesis. More precisely this thesis focuses on a photovoltaic driven lithium ion battery – hydrogen fuel cell hybrid system for energy storage. This system, as well as a system relying purely on lithium ion batteries for storage and a system relying purely on hydrogen as energy storage are simulated using the simulation software HOMER PRO. Additionally, the systems are simulated considering two different locations, one being the town of Tasiilaq in Greenland and the other being a workers accommodation near Doha, the capital of Qatar. The former requires both long-term and short-term energy storage, whilst the latter requires short term storage. Simulating the three system types in these two locations, allows for the analysis of the performance and applicability of the hybrid systems compared to the other systems under ...